High neutrophil/lymphocyte ratio is associated with poor renal outcomes in Japanese patients with chronic kidney disease. (1st January 2019) - Yoshitomi, Ryota; Nakayama, Masaru; Sakoh, Teppei; Fukui, Akiko; Katafuchi, Eisuke; Seki, Makiko; Tsuda, Susumu; Nakano, Toshiaki; Tsuruya, Kazuhiko; Kitazono, Takanari
Abstract: Background: Several studies have shown that the neutrophil/lymphocyte ratio (NLR) is a marker that reflects the state of systemic inflammation. A high NLR was reported to be associated with cardiovascular events and mortality. However, little is known about the association between NLR and kidney disease progression in patients with chronic kidney disease (CKD). Therefore, the aim of the present study was to determine whether NLR is associated with renal outcomes in CKD patients. Methods: This prospective observational study included 350 consecutive patients with stage 1–4 CKD treated between June 2009 and November 2016. Data were collected until June 2017. The endpoint was the composite of end-stage renal disease requiring dialysis or death. Subjects were divided into two groups according to high and low NLR levels. A Cox proportional hazards model was used to determine the risk factors for composite outcomes. Results: The composite endpoint was observed in 83 patients during the median follow-up period of 31.8 months: 29 in the low NLR group and 54 in the high NLR group. Multivariable analysis showed that the high NLR group had a significant increase in the hazard ratio (HR) for composite outcomes (HR 1.67, 95% confidence interval 1.02–2.77) compared with the low NLR group. Conclusion: The present study demonstrated that a high NLR was associated with poor renal outcomes, suggesting that NLR may be a useful marker for prognostic prediction in patients with CKD.